Influence of Nd:YAG Laser on the Bond Strength of Self-etching and Conventional Adhesive Systems to Dental Hard Tissues - Marimoto, A. K. [UNESP]; Cunha, L. A. [UNESP]; Yui, K. C. K. [UNESP]; Huhtala, M. F. R. L. [UNESP]; Barcellos, D. C. [UNESP]; Prakki, A.; Goncalves, S. E. P. [UNESP] (Operative Dentistry Inc, 2013)
Purpose: The aim of this study was to investigate the influence of Nd:YAG laser on the shear bond strength to enamel and dentin of total and self-etch adhesives when the laser was applied over the adhesives, before they were photopolymerized, in an attempt to create a new bonding layer by dentin-adhesive melting.Material and Methods: One-hundred twenty bovine incisors were ground to obtain flat surfaces. Specimens were divided into two substrate groups (n=60): substrate E (enamel) and substrate D (dentin). Each substrate group was subdivided into four groups (n=15), according to the surface treatment accomplished: X (Xeno III self-etching adhesive, control), XL (Xeno III + laser Nd:YAG irradiation at 140 mJ/10 Hz for 60 seconds + photopolymerization, experimental), S (acid etching + Single Bond conventional adhesive, Control), and SL (acid etching + Single Bond + laser Nd:YAG at 140 mJ/10 Hz for 60 seconds + photopolymerization, experimental). The bonding area was delimited with 3-mm-diameter adhesive tape for the bonding procedures. Cylinders of composite were fabricated on the bonding area using a Teflon matrix. The teeth were stored in water at 37 degrees C/48 h and submitted to shear testing at a crosshead speed of 0.5 mm/min in a universal testing machine. Results were analyzed with three-way analysis of variance (ANOVA; substrate, adhesive, and treatment) and Tukey tests (alpha=0.05). ANOVA revealed significant differences for the substrate, adhesive system, and type of treatment: lased or unlased (p<0.05). The mean shear bond strength values (MPa) for the enamel groups were X=20.2 +/- 5.61, XL=23.6 +/- 4.92, S=20.8 +/- 4.55, SL=22.1 +/- 5.14 and for the dentin groups were X=14.1 +/- 7.51, XL=22.2 +/- 6.45, S=11.2 +/- 5.77, SL=15.9 +/- 3.61. For dentin, Xeno III self-etch adhesive showed significantly higher shear bond strength compared with Single Bond total-etch adhesive; Nd:YAG laser irradiation showed significantly higher shear bond strength compared with control (unlased).Conclusion: Nd:YAG laser application prior to photopolymerization of adhesive systems significantly increased the bond strength to dentin.